Patient portal readiness among postpartum patients in a safety net setting - Wieland, Daryl; Gibeau, Anne; Dewey, Caitlin; Roshto, Melanie; Frankel, Hilary (Applied Clinical Informatics, 2017)
Background: Maternity patients interact with the healthcare system over an approximately ten-month interval, requiring multiple visits, acquiring pregnancy-specific education, and sharing health information among providers. Many features of a web-based patient portal could help pregnant women manage their interactions with the healthcare system; however, it is unclear whether pregnant women in safety-net settings have the resources, skills or interest required for portal adoption.Objectives: In this study of postpartum patients in a safety net hospital, we aimed to: (1) determine if patients have the technical resources and skills to access a portal, (2) gain insight into their interest in health information, and (3) identify the perceived utility of portal features and potential barriers to adoption.Methods: We developed a structured questionnaire to collect demographics from postpartum patients and measure use of technology and the internet, self-reported literacy, interest in health information, awareness of portal functions, and perceived barriers to use. The questionnaire was administered in person to women in an inpatient setting.Results: Of the 100 participants surveyed, 95% reported routine internet use and 56% used it to search for health information. Most participants had never heard of a patient portal, yet 92% believed that the portal functions were important. The two most appealing functions were to check results and manage appointments.Conclusions: Most participants in this study have the required resources such as a device and familiarity with the internet to access a patient portal including an interest in interacting with a healthcare institution via electronic means. Pregnancy is a critical episode of care where active engagement with the healthcare system can influence outcomes. Healthcare systems and portal developers should consider ways to tailor a portal to address the specific health needs of a maternity population including those in a safety net setting.Citation: Wieland D, Gibeau A, Dewey C, Roshto M, Frankel H. Patient portal readiness among postpartum patients in a safety net setting. Appl Clin Inform 2017; 8: 698–709 https://doi.org/10.4338/ACI-2016-12-RA-0204
Keywords: Patient portal; patient engagement; prenatal care; meaningful use; electronic medical records